Correction: National income accounting attributes and economic welfare. Evidence from Pakistan. - Shuang Yang; Muhammad Waris; Muhammad Kashif Nawaz; Cheng Chen; Ijaz Younis (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0301829.].